2010
DOI: 10.1016/j.abb.2010.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular hydrophobic regions in scavenger receptor BI play a key role in mediating HDL-cholesterol transport

Abstract: The binding of high density lipoprotein (HDL) to scavenger receptor BI (SR-BI) is responsible for whole-body cholesterol disposal via reverse cholesterol transport. The extracellular domain of SR-BI is required for HDL binding and selective uptake of HDL-cholesterol. We identified six highly hydrophobic regions in this domain that may be important for receptor activity and performed sitedirected mutagenesis to investigate the importance of these regions in SR-BI-mediated cholesterol transport. Non-conservative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 62 publications
2
54
0
Order By: Relevance
“…The importance of extracellular domain of SR-BI in cholesteryl ester uptake has been explored by the use of chimeric receptors ( 28 ), by insertion of epitope tags into various regions of the domain of SR-BI ( 29 ), by blocking antibody against the extracellular domain, and by mutations ( 30,31 ). However, the HDL binding site and the factors that regulate SR-BI-mediated cholesteryl ester uptake remain to be identifi ed.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of extracellular domain of SR-BI in cholesteryl ester uptake has been explored by the use of chimeric receptors ( 28 ), by insertion of epitope tags into various regions of the domain of SR-BI ( 29 ), by blocking antibody against the extracellular domain, and by mutations ( 30,31 ). However, the HDL binding site and the factors that regulate SR-BI-mediated cholesteryl ester uptake remain to be identifi ed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that formation of a productive HDL/SR-BI complex [25] depends on the correct alignment of specific lipoprotein and receptor domains and/or the capacity of the receptor to undergo appropriate conformational changes that permit efficient lipid transport. Several studies [2629], including our own [5,3032], have demonstrated the important contributions of specific extracellular regions of SR-BI in mediating the selective uptake of HDL-CE. Indeed, the recent availability of the X-ray crystal structure of the extracellular domain of LIMP-2 [33], a scavenger receptor that shares 30% sequence identity with SR-BI, provides the opportunity to better recognize key structural features of this domain that contribute to its cholesterol transport functions.…”
Section: Introductionmentioning
confidence: 98%
“…6G-J ). Because production of transgenic larvae is not suitable for high-throughput studies, in vitro reconstitution of selective carotenoid uptake by SCRB15 and Cameo2, such as has been achieved for cellular cholesteryl ester uptake by SR-BI (46)(47)(48), is required to examine the selectivity mechanism by point mutagenesis or analysis of chimeric genes of SCRB15 and Cameo2.…”
Section: Discussionmentioning
confidence: 99%